Field Measurements and Numerical Modeling of Wave Climate in the Pacific Coast of Costa Rica - Alfaro Chavarría, Henry Gustavo (2022)
The wave climate of the Pacific coast of Costa Rica displays singularities that are inadequately included in global numerical models of wave generation and propagation. This shortcoming increases the uncertainty associated with the analysis and prediction of wave climate estimations required for coastal applications. Based on wave data from the central and northern Pacific coast of Costa Rica, the aim of this work is to present the Wave Climate of the Pacific Coast (WCPC), a hybrid downscaling model derived from a reanalysis of regional NOAA wave data with in-situ (field) measurements of significant height, period, and direction of waves obtained over a 7 year period (2014-2021). Four calibrated reanalysis nodes were used to propagate waves from undefined depths to the coast, using hybrid downscaling techniques and the SWAN model. Node calibration was performed using field data obtained almost uninterruptedly between 2014 and 2017, as well as reanalysis of calibrated data between 2005 and 2019.The end product consists of more than 10 000 numerical nodes distributed along the northern and central Pacific coast of Costa Rica, each one with a 3-hour resolution time series of significant wave height, peak period and mean direction, over a 14-year period from 2005 to 2019. Model results were validated using field measurements at an independent site in the central Pacific coast, with a coefficient of determination (r²) and a Root Mean Squared Error (RMSE) for significant wave height of 0.472 and 24.3 centimeters between the modeled and reference data respectively. The WCPC represents a valuable asset for the coastal development in Costa Rica, and could also improve large scale models at regional and even global scales.